Seroprevalence and risk factors of Hepatitis B and Hepatitis C infections among pregnant women in the Asante Akim North Municipality of the Ashanti region, Ghana; a cross sectional study - Ephraim, Richard (Afr Health Sci, 2015)
BACKGROUND: Viral hepatitis is a serious public health problem affecting billions of people globally with maternal-fetal transmission on the rise. OBJECTIVES: This study sought to determine the prevalence and factors associated with hepatitis B virus (HBV) and hepatitis C virus (HCV) infections among pregnant women in the Asante Akim North Municipality, in the Ashanti region of Ghana. METHODS: In this cross-sectional study 168 pregnant women were recruited from the Agogo Presbyterian hospital. Blood samples were collected for the detection of Hepatitis B Surface Antigen (HBsAg) and anti-HCV antibodies. A pretested questionnaire was used to obtain demographic data and identify the risk factors associated with the two infections. RESULTS: Of the 168 participants studied, 16 (9.5%) tested positive for HBV and 13 (7.7%) tested positive for HCV representing 9.5% and 7.7% respectively. A participant tested positive for both HBV and HCV co-infection representing 0.6%. Undertaking blood transfusion, tattooing and sharing of needles were associated with hepatitis C infection (P=0.001). HBV was not associated with any of the risk factors (P>0.05). CONCLUSION: Our findings suggest a high prevalence of hepatitis B and hepatitis C among pregnant women; blood transfusion, tattooing and sharing of hypodermic needles were associated with hepatitis C infection. Measures to reduce the disease and transmission burden must be introduced.